The Application of Non-Discriminatory Principle of Age Limit for Job Seekers in Indonesia - Yunanto, Firman Panca; Iskandar, Hardian (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The application of the non-discriminatory principle of the age limit for job seekers in Indonesia is an important issue in an effort to realize justice and equality of employment opportunities. The age limit on job vacancies is a provision made by some companies regarding the age range of job applicants to be able to apply for jobs. The practice of age restriction in the recruitment process is still widely found, even though it has been prohibited in article 5 of Law No. 13 of 2003 concerning Manpower and the Circular Letter of the Minister of Manpower No. M/6/HK.04/V/2025. This study aims to examine the application of the principle of non-discrimination in the labor recruitment process and sanctions if the principle is not applied. In this study, normative legal research methods are used using a statute approach, a comparative approach, and a conceptual approach. The results of this study show that the application of the principle of non-discrimination in the labor recruitment process in Indonesia has not been fully effective due to weak supervision. The application of the principle of non-discrimination must not conflict with Law No. 13 of 2003 concerning manpower and Law of the Republic of Indonesia Number 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection which, if violated, can result in sanctions. Therefore, there is a need to strengthen the role of supervisory institutions as an effort to create an objective, fair, inclusive labor recruitment process that focuses on the competencies or skills of applicants regardless of age limits.